Silica Chloride and Boron Sulfonic Acid as Solid Acid Catalysts in Preparation of Ethers and Esters Under Solvent-Free Condition - Elham, Sedighinia; Sargoli Mozhgan, Zahed (Asian Journal of Chemistry, 2010)
Boron sulfonic acid was easily prepared from the reaction of boric acid and chlorosulfonic acid under solvent free condition. The prepared solid acid was supported on silica gel by simple grinding and used as efficient solid acid catalyst in the preparation of ethers from the aliphatic and aromatic alcohols. The ethers were prepared in high isolated yields and in lesser times. Silica chloride was prepared by refluxing of silica gel in thionyl chloride. The obtained solid acid was efficiently used for the conditions of alcohols to the corresponding ethers and acetyl esters in less reaction time and in high isolated yields.